Optimal strut-and-tie modelsi n reinforced concrete structures - Biondini, Fabio; Bontempi, Franco; Malerba, Pier Giorgio (Computer Assisted Methods in Engineering and Science, 2023)
A general solution of the diffusion problems which concern the R.C. structures, may be deduced by the limit analysis, by means of truss schemes suitable to model the load transfer mechanism. In particular such schemes allow us to share the carrying functions between concrete and steel reinforcement. Latest developments call this kind a solution Strut-and-Tie (S&T) modellization. In this paper a procedure for the automatic search for optima! S&T models in R.C. elements is proposed. A highly indeterminate pin-jointed framework of a given layout is generated within the assigned geometry of the concrete element and an optimum truss is found by the minimization of a suitable objective function. Such a function allows us to search for the optimum truss according to a reference behaviour (the principal stress field) deduced through a F.E.A. and assumed as representative of the given continuum. After having explained the theoretical principles and the mathematical formulation, some examples show the pratical application of the procedure and its capability in handling complex stress paths, through schemes which result rational and suitable for a consistent design.